PENGARUH PENGGUNAAN MEDIA SOSIAL INSTRAGRAM TERHADAP EFEKTIVITAS KOMUNIKASI INTERPERSONAL DAN KEMAMPUAN AKADEMIK MAHASISWA POLITEKNIK NEGERI BATAM - Fadya, Nabila Casta (Commed Jurnal Komunikasi dan Media, 2025)
The rise of digital technology, particularly social media, has significantly impacted communication and learning habits among students. Instagram, a popular platform focused on visual content, is widely utilized by students in various aspects of their academic and social lives. This study examines the impact of Instagram on the effectiveness of interpersonal communication and academic performance of students at Batam State Polytechnic. The research employs a quantitative approach, utilizing questionnaires for data collection. The findings indicate that Instagram usage does not significantly affect the effectiveness of interpersonal communication, with a t-count of 1.861, which is smaller than the t-table value of 1.987. This suggests that communication through Instagram does not replace more profound face-to-face interactions. Conversely, Instagram usage does have a significant effect on students’ academic performance, as reflected by a t-count of 3.222, which exceeds the t-table value of 1.987. Instagram is used by students primarily to access academic resources, references for assignments, and learning materials. This result aligns with the Uses and Gratifications Theory, which posits that students turn to Instagram to satisfy their informational and educational needs, rather than for deep social interactions. Interpersonal Communication Theory indicates that Instagram cannot substitute more meaningful face-to-face communication, particularly when it comes to emotional bonding and interaction depth. Meanwhile, New Media Theory highlights that while Instagram facilitates quick interactions, the quality of interpersonal communication remains restricted. This research offers valuable insights for educational institutions on how to guide the optimal use of social media in enhancing academic and communicative outcomes for students.